2020
DOI: 10.1101/2020.01.15.907766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fast and efficient generation of knock-in human organoids using homology-independent CRISPR/Cas9 precision genome editing

Abstract: CRISPR/Cas9 technology has revolutionized genome editing and is applicable to the organoid field. However, precise integration of exogenous DNA sequences in human organoids awaits robust knock-in approaches. Here, we describe CRISPR/Cas9-mediated Homologyindependent Organoid Transgenesis (CRISPR-HOT), which allows efficient generation of knock-in human organoids representing different tissues. CRISPR-HOT avoids extensive cloning and outperforms homology directed repair (HDR) in achieving precise integration of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 58 publications
(81 reference statements)
0
47
0
Order By: Relevance
“…44 Excitingly, Artegiani et al later reported a CRISPR-Cas9-mediated homology-independent organoid transgenesis (CRISPR-HOT) methodology for fast and efficient generation of knock-in human organoids. 45 Combining tubulin tagging with TP53 knockout revealed that TP53 is involved in controlling hepatocyte ploidy and mitotic spindle fidelity, providing evidence that TP53 mutation-induced aneuploidy may promote liver cancer. 45 Thus, organoid technology in combination with CRISPR/Cas9 strategy is a powerful tool to investigate cancer gene function in a human context.…”
Section: Study Of Liver Tumor Initiation and Progression Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Excitingly, Artegiani et al later reported a CRISPR-Cas9-mediated homology-independent organoid transgenesis (CRISPR-HOT) methodology for fast and efficient generation of knock-in human organoids. 45 Combining tubulin tagging with TP53 knockout revealed that TP53 is involved in controlling hepatocyte ploidy and mitotic spindle fidelity, providing evidence that TP53 mutation-induced aneuploidy may promote liver cancer. 45 Thus, organoid technology in combination with CRISPR/Cas9 strategy is a powerful tool to investigate cancer gene function in a human context.…”
Section: Study Of Liver Tumor Initiation and Progression Mechanismsmentioning
confidence: 99%
“…45 Combining tubulin tagging with TP53 knockout revealed that TP53 is involved in controlling hepatocyte ploidy and mitotic spindle fidelity, providing evidence that TP53 mutation-induced aneuploidy may promote liver cancer. 45 Thus, organoid technology in combination with CRISPR/Cas9 strategy is a powerful tool to investigate cancer gene function in a human context. 46 PDO liver tumoroids are also widely used to characterize the molecular mechanisms leading to tumor progression.…”
Section: Study Of Liver Tumor Initiation and Progression Mechanismsmentioning
confidence: 99%
“…One of the reported genome editing applications in human organoids is to create knock-in reporters by targeted and in-frame insertion of a fluorescence reporter to the gene of interest. 55,111 Expression of the fluorescence reporter, whether directly fused to the endogenous gene, or separated by a “self-cleaving” 2 A peptide, will be under the control of the endogenous promoter and enhancer. This is a useful approach to analyze kinetics of gene expression in real-time.…”
Section: Applications Of Genome Editing In Human Organoid Studiesmentioning
confidence: 99%
“…More recently, homology-independent targeted integration (HITI), was shown to efficiently induce base pair precise KIs in both dividing and non-dividing cells [11][12][13] by exploiting NHEJ and Cas9 cleaved donors, with exciting potential for gene editing applications in vivo 11,14 . Moreover, single base substitutions can also be achieved by using base editors (BEs) involving catalytically impaired Cas9 variants fused to cytosine or adenine deaminase 15,16 and, more recently, prime editors (PEs) using Cas9 nickase fused to reverse transcriptase, achieving genomic interventions with little to no indels and reducing the risks associated with DSBs 17 .…”
Section: Mainmentioning
confidence: 99%